ANALISIS MINOR INSPECTION PLTGU UNIT 1 PT. PLN NUSANTARA POWER UP BELAWAN TERHADAP PENINGKATAN NILAI EKONOMIS - Yan Bastian Lumbantobing; Pristisal Wibowo; Zuraidah Tharo (Jurnal Nasional Teknologi Komputer, 2025)
This study aims to analyze the impact of minor inspection implementation on increasing the economic value of PLTGU Unit 1 PT. PLN Nusantara Power UP Belawan, in this case PLTGU Unit 1 is the name of the GT 1.1 generator, the limitations of this study are directed at the performance parameters of the generator such as, specific gas consumption (SGC), heat rate, thermal efficiency, and net power output, to determine the impact of minor inspection implementation on increasing economic value. The results of the study showed that after minor inspection, there was a decrease in the specific gas consumption (SGC) value from 0.0120 mmBTU/kWh to 0.0119 mmBTU/kWh, a decrease in the heat rate value from 3,043.85 kCal/kWh to 3,027.76 kCal/kWh, an increase in thermal efficiency from 28.25% to 28.40%, in terms of electrical energy production, there was an increase in net power output from the previous 94,310 kWh to 94,390 kWh, this indicates an increase in net power output which contributes to increasing the availability of electricity supply to the system. Thus, minor inspection has been proven to provide a real contribution to increasing the economic value of the power plant, and is recommended to be carried out routinely according to the maintenance schedule.